Необитаемое сердце Северины - Васина Нина (Детектив не для всех, 2009)
Экземпляры: Аб (20091014) / Инвентарный номер: 95145 / Цена: 119.50 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: В 19 / ББК: 84(2Рос=Рус)6